Posterior labral repairs of the shoulder among baseball players: Results and outcomes with minimum 2-year follow-up - Kercher, J. S.; Runner, R. P.; McCarthy, T. P.; Duralde, X. A. (The American Journal of Sports Medicine, 2019)
Background: There is a paucity of information regarding the treatment of posterior labral tears of the shoulder for baseball players. Reports regarding treatment and postoperative outcomes are more limited than its anterior and superior counterparts. Purpose: To evaluate the clinical presentation, surgical findings, postoperative outcomes, and rate of return to sport after arthroscopic repair of posterior labral injuries of the shoulder among baseball players. Study Design: Case series; Level of evidence, 4. Methods: Retrospective review was performed of baseball players who underwent arthroscopic posterior labral repair between 2009 and 2015 by a single surgeon, with a minimum 2-year follow-up. The group was composed of 32 male patients involved in recreational (6.3%), high school (43.8%), college (31.3%), and professional (18.8%) baseball, with a mean age of 20.5 years. Patients were categorized by chief complaint, clinical findings, surgical findings, and concomitant procedures performed. Pre- and postoperative measures included pain scale, range of motion, American Shoulder and Elbow Surgeons shoulder score, return to play, and patient satisfaction. Results: A variety of tear patterns were identified; 32% involved 90° of the posterior superior labrum; 35% involved the posterior 180°; and 32% involved 90° of the posterior inferior labrum. The dominant mechanism of injury was throwing (34.4%). The most common chief complaint was pain (n = 25, 78%), followed by pain and instability symptoms (n = 6, 18.8%), with only 3% citing isolated sensation of instability. Magnetic resonance imaging clearly identified tear patterns in 75% of cases. American Shoulder and Elbow Surgeons scores significantly improved (P < .0001), increasing on average 30.9 points from the preoperative mean of 65.4 to a postoperative mean of 96.3. No significant range of motion deficits were noted. Tear size and number of anchors utilized did not influence outcomes. Ninety-four percent of athletes returned to play, 61% at previous levels, and 6% did not return. Pitchers had a lower return to previous level of play than position players (41% vs 86%, P = .0113). Conclusion: Arthroscopic treatment of posterior labral tears of baseball players was effective in improving pain and function, resulting in 94% patient satisfaction and 94% return to sport, with 61% returning to previous level of play. Patient presentation is variable, with a majority of patients citing pain rather than instability. Keywords shoulder, arthroscopy, posterior labral repair, baseball, throwers